Bond Behaviour of Reinforced Fly Ash-Based Geopolymer Concrete Beams - Chang, Ee Hui; Sarker, Prabir; Lloyd, Natalie; Rangan, B. Vijaya (Concrete Institute of Australia, 2009)
In view of sustainable development in the construction industry, investigation has been carried out on fly ash-based geopolymer concrete, which is an environmentally friendly material that uses geopolymer paste as binder instead of Portland cement. Previous studies on the engineering properties and structural behaviour of geopolymer concrete have shown promising potential of this material. This paper describes the bond behaviour between geopolymer concrete and reinforcing bars in tensile splices in beams. Twelve full-scale beam specimens with lap-spliced reinforcing bars were cast and tested in the laboratory to study the bond performance of geopolymer concrete. The effects of concrete compressive strength, bar diameter and splice length of the bars on bond strength of lap splices in geopolymer concrete were evaluated. Test results, including general behaviour of beams, failure modes and cracking patterns were gathered and analysed. Current analytical models and codes provision to predict bond strength for Ordinary Portland Cement (OPC) concrete were used to analyse the bond strength of test specimens. Good correlation between test and analytical results were found. This study also demonstrates the excellent potential of geopolymer concrete for use as a construction material.